2007
DOI: 10.1093/ndt/gfm300
|View full text |Cite
|
Sign up to set email alerts
|

Urinary excretion of endothelin-1 (ET-1), transforming growth factor- 1 (TGF- 1) and vascular endothelial growth factor (VEGF165) in paediatric chronic kidney diseases: results of the ESCAPE trial

Abstract: Children with CKD exhibit significantly elevated urinary excretion of ET-1, TGF-beta1 and VEGF(165) in comparison to healthy children. Urinary excretion of these biomarkers was most enhanced in patients with obstructive uropathies. A positive correlation between urinary TGF-beta1 and VEGF(165) excretion, shown both in patients and healthy controls, indicates an interdependent nature of their generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
5

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 29 publications
3
38
0
5
Order By: Relevance
“…38 O aumento da excreção desses mediadores correlacionou-se com a diminuição da taxa de filtração glomerular (TFG) e foi mais evidente nos pacientes com uropatias obstrutivas, refletindo o impacto da lesão túbulo-intersticial sobre a função renal global. 38 …”
Section: Inflamação E Doença Renal Crônicaunclassified
See 2 more Smart Citations
“…38 O aumento da excreção desses mediadores correlacionou-se com a diminuição da taxa de filtração glomerular (TFG) e foi mais evidente nos pacientes com uropatias obstrutivas, refletindo o impacto da lesão túbulo-intersticial sobre a função renal global. 38 …”
Section: Inflamação E Doença Renal Crônicaunclassified
“…participação de citocinas e quimiocinas em diferentes mecanismos de lesão ao tecido renal. [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Especificamente no tecido renal, as citocinas induzem proliferação local de células tubulares e intersticiais, síntese de matriz extracelular, atividade pró-coagulante do endotélio, formação de espécies reativas de oxigênio e aumento da expressão de moléculas de adesão e lípides biologicamente ativos. [24][25][26][27][28][29][30][31] A liberação de citocinas também se relaciona aos efeitos hemodinâmicos e locais da ativação do sistema renina angiotensina (SRA).…”
Section: Citocinas E Quimiocinasunclassified
See 1 more Smart Citation
“…A role for TGF-␤1 is implicated in the deposition of collagen that accompanies the progression of renal disease in rodent models. 34,35 It has also been reported that TGF-␤1 levels are particularly high in pediatric patients with renal insufficiency 36 and in black hypertensives with target organ damage. 2,37 We can find no reports describing an assessment of TGF-␤3 levels in patients with hypertension.…”
Section: Discussionmentioning
confidence: 98%
“…Substâncias que participam de passos chave da uropatia obstrutiva já foram estudadas com base no mecanismo em que participam: 1) resposta vascular: endotelina-1 , vascular endothelial growth factor VEGF (Grenda et al, 2007); 2) migração de leucócitos: proteína quimiotática de monócitos MCP-1 (Grandaliano et al, 2000;Bartoli et al, 2011;Stephan et al, 2002), interleucinas (Madsen et al, 2012); 3) fatores de crescimento: o fator de crescimento epidermal EGF (Oka et al, 1999;, o insulin-like growth factor-1 IGF-1 (Marshall et al, 1991;Serel et al, 2000) ; 4) disfunção tubular: kidney injury molecule-1 KIM-1 (Wasilewska et al, 2011), N-acetil-ß-D-glucosaminidase, γ-glutamil transferase e fosfatase alcalina (Everaert et al, 1998;Shokeir et al, 2009 ß2-microglobulina (Dommergues et al, 2000).…”
Section: Marcadores De Obstrução Do Trato Urináriounclassified